Depressive symptoms and 5-year incident metabolic syndrome among older adults - Qian Wu (Nature Portfolio, 2021)
Abstract Little is known regarding the association between depressive symptoms and metabolic syndrome (MetS) among older Chinese adults. This study aimed to examine the association of depressive symptoms with MetS and its components among Chinese elderly. Based on whether they showed depressive symptoms at baseline, 262 age-gender-matched participants from a community-based cohort study were included. The presence of depressive symptoms was measured using the nine-item Patient Health Questionnaire (PHQ-9). MetS was defined according to the Adult Treatment Panel III of the National Cholesterol Education Program. Linear regression and logistic regression analyses were performed to assess associations of depressive symptoms with MetS and its components. The incidence of MetS among the participants with depressive symptoms at baseline was 15.27% (20/131). The association of the presence of depressive symptoms with MetS was significant (odds ratio [OR] = 2.53, 95% confidence intervals [CI] = 1.07, 5.95). There was a negative association between depressive symptoms and hypertension (OR = 0.04, 95% CI = 0.002, 0.98). The change in mean arterial pressure varies approximately 1.03 mmHg with a 1-point change in PHQ-9 score. In this study, baseline depressive symptoms were associated with subsequent MetS. The presence of depressive symptoms was negatively associated with elevated mean arterial pressure.